Floating exchange rates and international monetary reform - Willett, Thomas D. (Washington, DC : American Enterprise Institute for Public Policy Research, 1977)
This book provides historical background on the evolution of the world's monetary system beginning with the Bretton Woods agreement in 1945. It then details the proposals for reform and the elaborate bureaucratic negotiations among national governments in various exotic international forums that began in the late 1960's and were brought to an anticlimax in Jamaica in 1976. The author describes the strong bias against floating exchange rates held by eminent economists such as Ragnar Nurkse, Gottfried Haberler and John Maynard Keynes arising out of their interwar experience with currency inconvertibility, commodity price fluctuations, and depression. All advocated that the new Bretton Woods system should have "stable" exchange parities, although they differed regarding the extent to which imbalances in international payments should be financed by capital movements (assumed to be carefully controlled) or met by official parity adjustments.
Includes bibliographical references.
usc 08/05/2018
Loans
Keywords: Foreign exchange rates; International finance; Foreign exchange